(untitled) (Al-Mansour Journal, 2023)
A shear wall was defined as a vertical structural element that transmits gravity loads to the foundation while resisting lateral loads caused by wind and seismic activity. Present study, the performance of reinforced lightweight concrete shear walls under the effect of seismic loads is considered with different loading types as static as equivalent static analysis and dynamic as time history analysis applied to reinforced concrete frame buildings with and without the presence of reinforced lightweight concrete shear walls. The models are simulated using the finite element method by SAP2000 software. Displacements, drifts, building performance, and base shear are evaluated for all cases of loading. The analysis results indicated that the presence of reinforced concrete shear walls led to reduced displacements, drifts, and increases in frequency under static seismic load and also reduced deformation under time history loading and an additional increase in base shear resistance with more stability and an increase in overall stiffness of the building. Also, include the results. The base shear resistance of Normal weight building with lightweight shear walls (NWB-LWS) is lower than that of Normal weight building with normal weight shear walls (NWB-NWS) due to the reduced building mass. The applied static and dynamic loadings did not cause any structural members to fail That is, by using different methods of seismic analysis. The difference in the weights of the different shear walls was about (19.7%).